The meso-fracturing mechanism of marble under unloading confining pressure paths and constant axial stress - Linna Sun (Nature Portfolio, 2021)
Abstract Failure tests on marble during unloading confining-pressure under constant axial stress and simulations with the particle flow code were performed. The influence mechanism of the unloading rate of the confining pressure, initial unloading stress, and confining pressure on the failure characteristics of, and crack propagation in, marble was studied. By using the trial-and-error method, the conversion relationship between the unloading rates of confining pressures in laboratory tests and numerical simulations was ascertained. Micro-cracks formed in the unloading process of confining pressure are dominated by tension cracks, accompanied by shear cracks. The propagation of shear cracks lags that of tension cracks. As the confining pressure is increased, more cracks occur upon failure of the samples. The proportion of shear cracks increases while that of tension cracks decreases. The failure mode of samples undergoes a transition from shear-dominated failure to conjugated shear failure.